Pengembangan perangkat pembelajaran visual thinking disertai aktivitas quick on the draw pada mata kuliah metode numerik - Septi Dariyatul Aini; Sri Irawati (STKIP PGRI Banjarmasin, 2018)
This research aims to produce learning kits for even numerical semester subjects with visual thinking learning accompanied by quick on the draw activities on student learning outcomes. This type of research is research on the development of ADDIE (Analysis; Design; Development; Implementation; Evaluation) models. The subjects of this study were lecturers and students of class A in the fourth semester of Mathematics Education at Madura University. This study produced learning tools in the form of RPM, LKM, and THB. From the results of expert validation, scores of observations of lecturer and student activities, learning outcomes tests, and student response questionnaires indicate that RPM, LKM, and THB are valid, practical, and effective. Valid because the coefficient of validity of RPM, LKM, and THB has an average value of 3,79. Practical because the average score of lecturer and student activity was 3,78 (very good) and 3,38 (good) respectively. And effective because the student response is 84,76% (positive); and the test results amounted to 85,71% (completed classically).